ANALISIS PENGARUH KETETAPAN HARGA, PROMOSI, DAN FASILITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN DI HOTEL YESTOYA WAY JEPARA LAMPUNG TIMUR - Buchori Buchori (Universitas Muhammadiyah Metro Lampung, 2015)
Companies that are able to compete in the market is the company that can provide quality products or services. So the company is required to continue to make improvements, especially in the quality of service. It is intended that all the goods or services being offered will have a good place in the eyes of the public as consumers and potential consumers. Because consumers in selecting goods and services based on the motivation that will affect the type, taste the goods and services purchased.Formulation of the problem in this research is